Core Trends in Engineering Education: Five Years of the “Synergy” International Conference - M. F. Galikhanov; S. V. Barabanova; A. A. Kaibiyainen (Высшее образование в России)
This article discusses the topical issues of engineering education, which have become the discussion point at the international network scientific and practical conference titled “Synergy” that has been held since 2016. The organizational basis of the conference is provided by the leading technical universities in Russia under the support of the international societies for engineering education and the largest Russian energy company Gazprom. The article outlines the broad issues of the conference, related to interdisciplinarity, new standards and technologies for engineering education, digital educational environment and online technologies, interaction between engineering education and high-tech business and industry, the models of digital competencies and mechanisms to independently certify them, training of highly qualified personnel, professional education within the school-university-enterprise system, and many other relevant aspects of contemporary engineering education.